2011
DOI: 10.1177/147323001103900325
|View full text |Cite
|
Sign up to set email alerts
|

Value of Diffusion-Weighted Imaging in Grading Tumours Localized in the Fourth Ventricle Region by Visual and Quantitative Assessments

Abstract: This study investigated visual and quantitative assessment of diffusion-weighted imaging (DWI) for grading tumours localized in the fourth ventricle region. Patients were diagnosed histopathologically and classified into two groups: those with high-grade (World Health Organization [WHO] grades III and IV) and those with low-grade tumours (benign, WHO grades I and II). DWI signal intensity was described using a five-point scale. Minimum apparent diffusion coefficient (ADC) values were obtained from areas with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…This feature is most likely due to the fact that medulloblastomas are characterized by a high degree of cellularity and often contain cells with a high nuclear:cytoplasmic ratio, which provides an increased number of membrane barriers to microscopic water diffusion 14,15 . While not conclusive, recent work has suggested that ADC maps may be useful to noninvasively diagnose medulloblastoma using this characteristic [8][9][10]12,13,[16][17][18][19][20][21][22] . A number of methods exist for measuring water diffusivity in tumors.…”
Section: Image Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…This feature is most likely due to the fact that medulloblastomas are characterized by a high degree of cellularity and often contain cells with a high nuclear:cytoplasmic ratio, which provides an increased number of membrane barriers to microscopic water diffusion 14,15 . While not conclusive, recent work has suggested that ADC maps may be useful to noninvasively diagnose medulloblastoma using this characteristic [8][9][10]12,13,[16][17][18][19][20][21][22] . A number of methods exist for measuring water diffusivity in tumors.…”
Section: Image Analysismentioning
confidence: 99%
“…A number of methods exist for measuring water diffusivity in tumors. These methods include measuring the minimum ADC value (hereafter termed ADC min ) within the entire tumor 15,18,19 , measuring the average ADC value within the entire tumor or within contrastenhancing portions of tumor 20,23,24 , normalizing ADC values within the tumor to those in normal tissue (hereafter referred to as nADC) 8,14,24 and using ADC histograms 12 . Most studies of nADC values are performed in a quantitative manner but some studies have measured nADC values by qualitative visual inspection 17,19 .…”
Section: Image Analysismentioning
confidence: 99%
See 3 more Smart Citations